Recommendations improving the Staffsâ Job Satisfaction of the Public Organizations In Dong Nai Province - Nguyen Thi Phuong Thao, Phan Thanh Tam, (Social Science Learning Education Journal, 2017)
: The level of employee satisfaction is one of the criteria to evaluate the success of many Public Organizations. When employees are satisfied with their work, they will work more effectively and more closely with the Public Organizations. Moreover, if the Public Organizations will improve the level of employee satisfaction, the human resources will be maintained stable, helping to reduce operating costs and increase job performance. However, keeping employees happy is not just a pay rise. There are many simple, inexpensive solutions that help managers improve their satisfaction and increase employee engagement. The study results showed that there were 200 staffs related to the public organizations in Dong Nai province who interviewed and answered about 21 questions but 159 staffs processed. Data collected from July 2016 to November 2017 for the staffs of the public organizations in Dong Nai province. The paper had been analyzed KMO test, Cronbachs Alpha and the result of KMO analysis which used for multiple regression analysis. Staffsâ responses of the public organizations measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 1.000 the staffs of the public organizations in Dong Nai province. In addition, the exploratory factor analysis (EFA) results showed that there were five factors affecting the staffsâ job satisfaction of the public organizations in Dong Nai province with significance level 5 percent. We have recommendations improving the staffsâ job satisfaction of the Public Organizations in Dong Nai Province.Â Keywords: Job satisfaction, public, organizations and LHU